Synthesis of Thiophene Derivative and its Use as Zinc Metal Corrosion Inhibitor in Hydrochloric Acid Solution - Assad, Noora; Abdul-Hameed, Fatma; Yousif, Emad; Balakit, Asim (Al-Nahrain Journal of Science, 2018)
N-[(3-Bromo-2-methylthiophen-5-yl)methylene]-4-methoxyaniline) (5) has been synthesized and used as corrosion inhibitor for zinc metal in 2 M HCl at room temperature by using weight loss measurements. The obtained results showed that (5) is a good inhibitor and its inhibition efficiency (IE %) increased with the increase of inhibitor concentration. The surface coverage was 1.55 at 500 ppm inhibitor concentration; hence the optimum concentration was 500 ppm. Theoretical calculations investigate by studying the relationship between molecular structure and inhibition efficiency using semi-empirical molecular quantum calculations within the PM3 method as implemented in HyperChem package.